Where is commercial farming expanding in Mozambique? Evidence from agricultural surveys - Steven M. Glover; Vincenzo Salvucci; Sam Jones (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper studies the dynamics of the agricultural sector in Mozambique, focusing on the role of commercial farms. Using agricultural survey data from 2002 to 2012, we analyse the spatial distribution of large farms and identify factors influencing their location decisions. We find that the spatial dispersion of large farms across the country is not uniform. Large farms tend to be located in wealthier and more educated areas, with better road access and higher levels of population density. Given an increasing volume of investments in the agricultural sector in Mozambique, a better understanding of these spatial trends can shed light on the processes through which large commercial farming entities may influence smallholder agricultural production and rural welfare.
Keywords: Q10; Q12; Q15; R12; R14; 330; agriculture; large commercial farms; spatial localization